A trajetória docente de uma alfabetizadora do Colégio São José em Pelotas/RS nas décadas de 1940 a 1980 - Louzada, Maria Cristina dos Santos (2012)
The present work a is historical research with a biographical approach to investigate the life of a literacy - Sister Maria Luisa - during the time she served on the St. Joseph College in Pelotas / RS. We sought to analyze her memories through interviews and documents that describe her teaching method developed and how were her lessons from the acquisition of literacy to the reading and writing by students. For this end, we considered the historical context, social and cultural relations that developed between the teacher and students, linking them to their teachers during the 1940s until 1980. This research has also aimed to analyze why the literacy felt the need to create a proprietary method to develop skills in teaching reading and writing in the classroom. For historians of education, biographical research are very important because they tend to reveal the school contexts, teachers' views on their actions and contribute to the processes of teacher training. In this research, the main source used are the narratives of life and work of Sister Maria Luisa. I conducted four interviews with the teacher, in which she recalled the facts of his 42 years of literacy. In addition, interviews were made with three former students of the educator and an interview with a professional colleague who used his method to teach literacy. Another important source, however, were the personal files. Exploiting document is considered extremely valuable in historical research, behold, it can be found through subsidies for interpreting the facts more accurately. In this research, we found something very valuable: a primer "Castle of Knowledge", representing the method created by the teacher to conduct a literacy model that held the attention and stimulate students in learning to read and write. Through the narratives collected, I conclude that the pedagogical method used by Sister Maria Luisa in the classroom is the mark of her career, unforgettable for all who were associated with her. With the firm intention of uncovering the past and make public the personality and the work of a recognized teacher in the school community where she worked, which is sought to find out about their memories. Please note that this is an overview of the sources. May, from this work, shape new ways of interpreting the narratives.